Anticorpos contra o herpesvírus canino tipo 1 em cães domiciliados e de abrigos no Rio Grande do Sul - Augusti, Letícia Maffi (2017)
Canine herpesvirus type 1 (CHV-1) is associated with reproductive disorders and neonatal mortality. CHV-1 is widely distributed and is considered enzootic in the dog population. Occurrence of infection in the country is unknown, and thus the real need for additional prevention measures, such as vaccination, is unknown. Therefore, the aim of this study was to investigate the presence of antibodies against CHV-1 in serum samples of domestic and sheltered dogs of different regions from Rio Grande do Sul state. For this, 914 serum samples from domestic dogs from Santa Maria (332 dogs obtained from Hospital Veterinário Universitário - HVU / UFSM and 381 from in the anti-rabies vaccination campaign), a veterinary clinical laboratory in Porto Alegre (n=43) and 158 from shelters dogs of Passo Fundo (n=98) and Cachoeira do Sul (n=60). Serum samples were tested by virus-neutralization test (VN) for CHV-1 antibodies. Neutralizing antibodies against CHV-1 in titers equal or higher than 4 were detected in 66,9% (612/914) of the samples. Among household dogs, 79,5% (264/332) from HVU/UFSM and 57.2% (218/381) from the vaccination campaign. Among the samples collected in the clinical laboratory in Porto Alegre, 41.8% (18/43) had antibodies to CHV-1. Among the sheltered dogs, 72.4% (71/98) of samples from Passo Fundo and 68.3% (41/60) from Cachoeira do Sul had antibody to CHV-1. The antibody titers ranged among the groups, but many samples had titers higher than 128. Since there are no commercial vaccines against CHV-1 in Brazil, the presence of neutralizing antibodies indicates the circulation of CHV-1 in the investigated population. Based on these findings, control measures, prevention, immunization and the need for a correct diagnosis should be considered.